1992
DOI: 10.1111/j.1365-3083.1992.tb03256.x
|View full text |Cite
|
Sign up to set email alerts
|

Presence of CD 16 on Endothelial Cells in Heart Transplant Rejection: an Immunohistochemical Study

Abstract: We studied the distribution of Fc gamma RIII (CD16) in human lymphoid and non-lymphoid tissue by immunohistochemistry and two-colour immunofluorescence. In all tissues except stomach, skin, muscle and heart, infiltrating cells were stained. In tonsil and thymus, the CD16 antibody CLBgran 1 labelled some cells with high endothelial morphology in T-cell areas. Two-colour fluorescence combination of CD16 and antibody to Von Willebrand factor confirmed the endothelial nature of the CLB gran 1-positive cells. Fc ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The discrepancy may be ascribed to the difference in study material, and state of activation of the endothelial cells. Elsewhere we have reported on the presence of FcyR class 111 on endothelium in endomyocardial biopsies from patients after heart transplantation that correlated with rejection of the transplant (44). This indicates that the expression of FcyR by endothelium is associated with a state of activation of the cells.…”
Section: Discussionmentioning
confidence: 80%
“…The discrepancy may be ascribed to the difference in study material, and state of activation of the endothelial cells. Elsewhere we have reported on the presence of FcyR class 111 on endothelium in endomyocardial biopsies from patients after heart transplantation that correlated with rejection of the transplant (44). This indicates that the expression of FcyR by endothelium is associated with a state of activation of the cells.…”
Section: Discussionmentioning
confidence: 80%
“…Fcg receptors type II and III have been demonstrated in EC in placenta [21], lymphoid tissues, and nerves [22]. The presence of Fcg receptors or FcgR-like bindings has been reported on virusinfected EC [23], neutrophil lysate injured EC [19], as well as EC in transplant hearts undergoing rejection [24]. However, several studies failed to confirm the presence of FcgR on other normal vascular EC [21].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, nonstimulated human EC may express low levels of FcgRII and FcgRIII. According to reports, anti-FcgRII and anti-FcgRIII bound to endothelium of nerve vessels [28], placental villi [29], and endocardium of hearts undergoing rejection [24].…”
Section: Discussionmentioning
confidence: 99%
“…We also observed a higher number of interstitial CD16+ cells associated with peritubular capillaritis. A previous study found a significant correlation between CD16+ cells in myocardial capillaries and heart transplant rejection suggesting that the presence of FcγRIIIA on capillaries may indicate endothelial activation …”
Section: Discussionmentioning
confidence: 96%